2007
DOI: 10.1016/j.neuron.2006.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-Stimulated Adenylyl Cyclases Regulate ERK-Dependent Activation of MSK1 during Fear Conditioning

Abstract: The cAMP and ERK/MAP kinase (MAPK) signal transduction pathways are critical for hippocampus-dependent memory, a process that depends on CREB-mediated transcription. However, the extent of crosstalk between these pathways and the downstream CREB kinase activated during memory formation has not been elucidated. Here we report that PKA, MAPK, and MSK1, a CREB kinase, are coactivated in a subset of hippocampal CA1 pyramidal neurons following contextual fear conditioning. Activation of PKA, MAPK, MSK1, and CREB is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
168
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(189 citation statements)
references
References 37 publications
13
168
1
2
Order By: Relevance
“…To provide subcellular localization and confirmation of synaptosomal fractionation results, immunohistochemical co-localization of AC1 or AC8 was performed with protein markers and methods that have been successfully utilized to distinguish pre-and postsynaptic sites (Serpinskaya et al, 1999,Fukaya and Watanabe, 2000,Lachamp et al, 2005,Sindreu et al, 2007. Co-expression of AC1 and PSD-95 was observed within multiple structures of the hippocampus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To provide subcellular localization and confirmation of synaptosomal fractionation results, immunohistochemical co-localization of AC1 or AC8 was performed with protein markers and methods that have been successfully utilized to distinguish pre-and postsynaptic sites (Serpinskaya et al, 1999,Fukaya and Watanabe, 2000,Lachamp et al, 2005,Sindreu et al, 2007. Co-expression of AC1 and PSD-95 was observed within multiple structures of the hippocampus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine PKA activity, we assessed phosphorylated PKA substrate (pPKA-s) levels. Changes in pPKA-s immunoreactivity are reported to be a reliable and sensitive measure of altered PKA activity (26). As is shown in Fig.…”
Section: Unilateral Glucocorticoid Administration Into the Mpfc Does Notmentioning
confidence: 90%
“…Recent studies have shown that MSK1 is activated during contextual fear conditioning (Sindreu et al 2007) and that MSK1 Cold Spring Harbor Laboratory Press on April 6, 2019 -Published by learnmem.cshlp.org Downloaded from deletion impairs fear conditioning as well as spatial memory (Chwang et al 2007). MSK1 2/2 mice have a deficiency in hippocampal histone H3 phosphorylation and acetylation (Chwang et al 2007) and CREB-dependent transcription (Wiggin et al 2002), three events that are linked to both dendritic plasticity and memory (Hsieh and Gage 2005;Levenson and Sweatt 2005).…”
Section: Msk Learning and Memorymentioning
confidence: 99%